Atmospheric blocks modulate the odds of heavy precipitation events in Europe - Lenggenhager, Sina; Martius, Olivia (Climate Dynamics, 2019)
A statistical link is presented between atmospheric blocks in the Euro-Atlantic sector and the frequency of regional-scale heavy precipitation events in Europe. Changes in the odds of European 1-, 3- and 5-day accumulation heavy precipitation in the presence of a block are investigated for different geographical locations of blocks and for summer and winter. The results show a significant modulation of the odds of heavy precipitation events during blocking episodes over the North-Atlantic and Europe. Blocks located further east have only limited effects on the odds of heavy precipitation events over Europe. The spatial patterns are very diverse and are strongly dependent on the location of the blocks and on the season. Generally, the odds of heavy precipitation events are reduced in the area of the blocking anticyclone and increased in the areas southwest to southeast of it and in some cases also north of it. Often areas with increased odds of heavy precipitation coincide with the location of the storm track.